Catalyst as well as preparation method and application thereof

By adopting a four-layer hollow spherical shell structure, combined with graphitized carbon support, active metal layer and carbon layer protective layer, the problem of difficult to take into account the activity and durability of platinum carbon catalysts is solved, and an efficient fuel cell catalyst is achieved.

CN119601694APending Publication Date: 2025-03-11STATE POWER INVESTMENT CORP HYDROGEN ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411832336.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Platinum carbon catalysts have problems in both activity and durability in fuel cells, and the corrosion of carbon support and the aggregation, degradation and shedding of platinum affect its performance.

Method used

The interlayer multifunctional catalyst is adopted, and it has four layers of hollow spherical shell structure, including a graphitized hollow porous spherical shell-like carbon support, two layers of active metal layers and carbon layer protective layer. The active metal is supported by vacuum synthesis and undergoes two-stage heat treatment to form a stable catalyst structure.

Benefits of technology

A balance between activity and durability of the catalyst is achieved, slowing the agglomeration and shedding of the catalyst, and improving its performance and stability in fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601694A_ABST
    Figure CN119601694A_ABST
Patent Text Reader

Abstract

The invention discloses a catalyst and a preparation method and application thereof.The catalyst is of a hollow spherical shell structure, and the hollow spherical shell structure is sequentially provided with a protective layer, a first active metal layer, a carrier layer and a second active metal layer from outside to inside in the spherical diameter direction; wherein the protective layer is a carbon layer, and the carrier layer is a porous carbon layer. The catalyst disclosed by the invention is an interlayer type multifunctional catalyst, is of a four-layer hollow spherical shell structure, and is provided with a graphitized hollow porous spherical shell-shaped structure carbon carrier, so that the activity of the catalyst and the corrosion resistance of the carrier can be improved; the two active metal layers are respectively arranged on two sides of the carrier layer, so that activity and durability can be balanced, and agglomeration and falling of the catalyst are slowed down; a carbon layer protection layer is arranged outside the active metal layer, so that mass transfer is improved, a protection effect and a range limiting effect are achieved, and agglomeration and falling of active metal particles are reduced; the four-layer structure synergistically improves the activity and durability of the catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of fuel cells, and in particular to a catalyst and a preparation method and application thereof. Background Art

[0002] Fuel cells, as an efficient and clean energy conversion technology, have received widespread attention in recent years. In fuel cells, catalysts play a vital role. Their role is to accelerate the electrochemical reaction of hydrogen and oxygen by reducing the activation energy of the chemical reaction, thereby generating current. Platinum-carbon catalysts have become one of the most commonly used catalysts in fuel cells due to their excellent catalytic performance.

[0003] However, in practical applications, platinum-carbon catalysts face the problem of balancing activity and durability. On the one hand, in order to improve activity, the dispersion of platinum needs to be increased, but this will reduce its durability; on the other hand, in order to improve durability, the particle size of platinum needs to be increased, but this will reduce its activity. In addition, due to the harsh operating conditions of fuel cells, such as high temperature, high humidity and chemical reactions, the catalyst may experience corrosion of the carbon carrier and agglomeration, degradation and shedding of platinum during long-term operation, further affecting its performance.

[0004] Therefore, designing economical carbon-supported platinum-based catalysts with both high activity and durability and simple synthesis process remains an urgent problem to be solved. Summary of the invention

[0005] The present invention is based on the inventors' discovery and understanding of the following facts and problems: in practical applications, platinum-carbon catalysts have problems such as difficulty in balancing activity and durability, corrosion of carbon carriers, and agglomeration, degradation and shedding of platinum.

[0006] In order to solve the above problems, current research is mainly divided into the following directions: First, by changing the shape and size of platinum, optimizing its dispersion and particle size, so as to achieve a balance between activity and durability; second, by changing the structure and properties of the carbon carrier, the overall stability of the catalyst is improved. For example, using carbon nanotubes or graphene as carriers, due to their unique electronic structure and mechanical strength, they can have better corrosion resistance; third, by introducing a second component, such as cobalt, palladium, rhodium, etc., to form an alloy catalyst. This multi-component alloy catalyst can utilize the synergistic effect between metals, which can not only improve the catalytic activity, but also enhance the corrosion resistance of the catalyst. Although the above methods have improved the problem to a certain extent, the coping strategies are relatively simple or the processes are relatively complicated, and there are some problems in the above three research directions: for example, the activity and durability of the catalyst are not only related to the shape and size of platinum, but also affected by other factors, such as the agglomeration and shedding of platinum particles, which cannot fundamentally solve the activity and durability problems of the catalyst; only considering changing the structure and properties of the carbon carrier, carbon nanotubes and graphene and other carriers were introduced. When carbon nanotubes and graphene are used as carbon carriers, there are problems with poor platinum loading capacity and poor dispersion; the current preparation process of alloy catalysts is relatively complicated, making it difficult to achieve large-scale production.

[0007] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the embodiments of the present invention propose a catalyst and a preparation method and application thereof, wherein the catalyst is a sandwich-type multifunctional catalyst, presenting a four-layer hollow spherical shell structure, and having a hollow porous spherical shell structure carbon carrier that has been graphitized, which can improve the activity of the catalyst and the corrosion resistance of the carrier; two layers of active metal layers are respectively arranged on both sides of the carrier layer, which can balance the activity and durability, and slow down the agglomeration and shedding of the catalyst; a carbon layer protective layer is arranged outside the active metal layer, which plays a protective and confining role while improving mass transfer, and reduces the agglomeration and shedding of active metal particles; the four-layer structure synergistically improves the activity and durability of the catalyst.

[0008] An embodiment of the present invention provides a catalyst, which has a hollow spherical shell structure. The hollow spherical shell structure is provided with a protective layer, a first active metal layer, a carrier layer, and a second active metal layer in sequence from the outside to the inside along the spherical diameter direction; wherein the protective layer is a carbon layer, and the carrier layer is a porous carbon layer.

[0009] Advantages and technical effects brought by the catalyst of the embodiment of the present invention: the catalyst is a sandwich-type multifunctional catalyst with a four-layer hollow spherical shell structure. The catalyst has a hollow porous spherical shell structure carbon carrier with a large specific surface area, which can provide abundant active metal loading sites. The first active metal layer and the second active metal layer are respectively dispersed on the inner and outer sides of the carrier layer, which can balance the activity and durability; wherein, the outer first active metal layer is conducive to improving the mass transfer characteristics, and the inner second active metal layer is conducive to improving the kinetic activity, and the catalyst performance is better. And compared with the catalyst loaded with a single layer of active metal, the catalyst of the present invention can effectively slow down the agglomeration and shedding of the catalyst. A carbon layer protective layer is provided outside the active metal layer, which can protect the active metal layer from being poisoned by sulfonic acid groups while improving mass transfer. The protective layer also plays a limiting role, reducing the agglomeration and shedding of active metal particles. Each layer of the structure has an independent function, and at the same time, the four layers can synergistically improve the activity and durability of the catalyst.

[0010] In some embodiments, the carrier layer has a graphitized structure; the carrier layer includes graphite crystallites, and the size of the graphite crystallites is 1.5-3.5 nm;

[0011] And / or, the thickness of the carrier layer is 10-20 nm;

[0012] And / or, the inner diameter of the carrier layer is 50-500 nm;

[0013] And / or, the specific surface area of ​​the carrier layer is 600 to 1200 m 2 / g;

[0014] And / or, the mesopore volume of the carrier layer is 1.0 to 2.0 m 3 / g.

[0015] In some embodiments, the first active metal layer and the second active metal layer are each independently a single metal layer and / or an alloy metal layer; preferably, the first active metal layer and the second active metal layer each independently include at least one of Pt, PtCo, PtNi, and PtRu;

[0016] and / or, the total loading amount of the first active metal layer and the second active metal layer in the catalyst is 30-80wt%;

[0017] and / or, the loading amount of the second active metal layer in the catalyst is not less than 30% of the total loading amount of the first active metal layer and the second active metal layer in the catalyst;

[0018] And / or, the first active metal layer includes a first active metal, and the grain size of the first active metal is 2.5-6.5 nm;

[0019] And / or, the second active metal layer includes a second active metal, and the grain size of the second active metal is 2.5-6.5 nm.

[0020] In some embodiments, the protective layer has a thickness of 1-3 nm.

[0021] An embodiment of the present invention provides a method for preparing a catalyst, comprising the following steps:

[0022] (1) mixing a template, a first carbon precursor and a solvent, and stirring to form a precipitated product;

[0023] (2) calcining the precipitated product to obtain a calcined product; mixing the calcined product with a detergent to remove the template agent to obtain a carbon carrier;

[0024] (3) loading the carbon carrier with active metal through vacuum synthesis treatment, and then performing a two-stage heat treatment to obtain a heat-treated product; wherein the two-stage heat treatment includes a first stage heat treatment and a second stage heat treatment, and the temperature of the second stage heat treatment is higher than the temperature of the first stage heat treatment;

[0025] (4) Immersing the heat-treated product in a second carbon precursor solution, followed by drying and sintering to obtain a catalyst.

[0026] In the embodiment of the present invention, the template and the first carbon precursor form a precipitation product, and a carbon carrier having both a graphitized structure and a porous structure, i.e., a carrier layer, can be obtained by calcination. Compared with the method of first removing the template and then high-temperature graphitization treatment, the method of first calcining and then removing the template in the present invention can ensure the morphology of the material during high-temperature activation, so that it is not easy to collapse. Compared with the traditional method of synthesizing active metal layers, the present invention adopts a vacuum synthesis method to load active metals to obtain an active metal layer loaded on both sides of the carrier layer. The vacuum synthesis method can load active metal particles to the inner side of the carrier layer, and can also increase the inner active metal loading to form a second active metal layer. The second active metal layer is located on the inner side of the carrier layer, and is not easy to agglomerate, migrate, and fall off; compared with a single active metal layer, the combination of the inner and outer two layers of active metal layers is more conducive to improving the activity and durability of the catalyst. After the vacuum synthesis treatment loads the active metal, a two-stage heat treatment process is performed to obtain a catalyst with suitable and uniform particle sizes of the first active metal and the second active metal, and better performance. Finally, the protective layer is formed by immersing in a second carbon precursor solution, followed by drying and sintering, which not only improves mass transfer, but also plays a protective and confining role. The preparation method of the present invention is simple and efficient, and the template cost is low, which is conducive to large-scale production and application.

[0027] In some embodiments, in step (1), the template comprises at least one of mesoporous silica and tetraethyl orthosilicate;

[0028] And / or, in the step (1), the first carbon precursor comprises a first component and a second component; the first component comprises at least one of dopamine hydrochloride, resorcinol, m-aminophenol, and acrylonitrile; the second component comprises at least one of formaldehyde and acetaldehyde; the mass ratio of the first component to the second component is 1:(1-6);

[0029] And / or, in the step (1), the mass ratio of the template to the first carbon precursor is (2-8):1;

[0030] And / or, in the step (2), the calcination atmosphere includes a first gas, and the first gas includes at least one of water vapor, carbon dioxide, and air; in the calcination atmosphere, the volume percentage of the first gas is 10%-50%;

[0031] And / or, in the step (2), the calcination temperature is 1000-2500°C;

[0032] And / or, in step (2), the calcination treatment time is 1 to 6 hours;

[0033] And / or, in step (2), the detergent comprises an aqueous sodium hydroxide solution or an aqueous hydrofluoric acid solution.

[0034] In some embodiments, in step (3), the temperature of the first heat treatment is 80 to 200° C., and the time of the first heat treatment is 1 to 12 hours;

[0035] And / or, the temperature of the second heat treatment is 800-950°C, and the time of the second heat treatment is 0.5-3h;

[0036] And / or, the two-stage heat treatment is performed under an inert atmosphere.

[0037] In some embodiments, in step (4), the second carbon precursor includes at least one of polyvinyl alcohol, polyethylene glycol, dopamine hydrochloride, and tannic acid;

[0038] and / or, the concentration of the second carbon precursor solution is 0.1-10wt%;

[0039] And / or, the sintering temperature is 300-900°C, and the sintering time is 0.5-5h;

[0040] And / or, the sintering atmosphere is an inert atmosphere.

[0041] The embodiment of the present invention provides an application of a catalyst, wherein the catalyst includes the catalyst described in the embodiment of the present invention or the catalyst prepared by the preparation method described in the embodiment of the present invention, and the catalyst is used in a fuel cell. In the embodiment of the present invention, the catalyst has excellent activity and durability.

[0042] The embodiment of the present invention provides a fuel cell, comprising the catalyst provided by the embodiment of the present invention or the catalyst prepared by the preparation method provided by the embodiment of the present invention. In the embodiment of the present invention, the catalyst has excellent activity and durability. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 It is a schematic structural diagram of the catalyst of the present invention. DETAILED DESCRIPTION

[0044] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.

[0045] like Figure 1 As shown, a catalyst of an embodiment of the present invention has a hollow spherical shell structure, and the hollow spherical shell structure is provided with a protective layer, a first active metal layer, a carrier layer, and a second active metal layer in sequence from the outside to the inside along the direction of the spherical diameter (spherical radius); wherein the protective layer is a carbon layer, and the carrier layer is a porous carbon layer.

[0046] The catalyst of the embodiment of the present invention is a sandwich-type multifunctional catalyst with a four-layer hollow spherical shell structure. The catalyst has a hollow porous spherical shell structure carbon carrier with a large specific surface area, which can provide abundant active metal loading sites. The first active metal layer and the second active metal layer are respectively dispersed on the inner and outer sides of the carrier layer, which can balance the activity and durability; wherein, the outer first active metal layer is beneficial to improving the mass transfer characteristics, and the inner second active metal layer is beneficial to improving the kinetic activity, and the catalyst performance is better. And compared with the catalyst loaded with a single layer of active metal, the catalyst of the present invention can effectively slow down the agglomeration and shedding of the catalyst. A carbon layer protective layer is provided outside the active metal layer, which can protect the active metal layer from being poisoned by sulfonic acid groups while improving mass transfer. The protective layer also plays a limiting role, reducing the agglomeration and shedding of active metal particles. Each layer of the structure has an independent function, and at the same time, the four layers can synergistically improve the activity and durability of the catalyst.

[0047] In some embodiments, the catalyst has a hollow porous spherical shell carrier (i.e., a carrier layer), the outer surface of the hollow porous spherical shell carrier is loaded with a first active metal layer, the first active metal layer is coated with a protective layer on the outside, and the inner surface of the hollow porous spherical shell carrier is loaded with a second active metal layer; optionally, the hollow porous spherical shell carrier can be spherical or ellipsoidal.

[0048] In some embodiments, the hollow spherical shell structure may be spherical or ellipsoidal.

[0049] In some embodiments, the carrier layer has a graphitized structure; the carrier layer includes graphite crystallites, and the size of the graphite crystallites is 1.5-3.5nm, specifically, for example, 1.5nm, 2.5nm, 3.5nm. In the embodiments of the present invention, the carbon carrier has a relatively stable graphitized structure, the size of the graphite crystallites is 1.5-3.5nm, has strong corrosion resistance, and the durability of the catalyst is significantly improved; at the same time, it has excellent electronic conductivity, which helps to increase the electrochemical reaction rate. When the size of the graphite crystallites is less than 1.5nm, the corrosion resistance of the carbon carrier is relatively poor; when the size of the graphite crystallites is greater than 3.5nm, the loading capacity of the carbon carrier decreases, which is not conducive to the loading and dispersion of the catalyst.

[0050] In some embodiments, the support layer is a porous carbon layer; optionally, the porous carbon layer includes carbon elements and other elements, such as nitrogen elements.

[0051] In some embodiments, the thickness of the support layer is 10-20 nm, specifically, for example, 10 nm, 15 nm, 20 nm. In the embodiment of the present invention, the thickness of the support layer is 10-20 nm, the structure is more stable, and there are more pore structures on the surface, which can ensure the catalyst loading inside the carbon layer. When the thickness of the support layer is less than 10 nm, the support is unstable and easy to deform and collapse. When the thickness of the support layer is greater than 20 nm, the number of through holes on the carbon layer is relatively small, which is not conducive to the loading of the active metal in the inner layer.

[0052] In some embodiments, the inner diameter of the carrier layer is 50-500nm, wherein the inner diameter is the diameter of the inner side of the carrier layer, specifically, the inner diameter of the carrier layer can be 50nm, 80nm, 100nm, 200nm, 300nm, 400nm, 500nm, preferably, 80-200nm. In an embodiment of the present invention, the carrier layer is a hollow porous carbon ball layer, and the inner diameter of the carrier layer is 50-500nm, that is, the size of the hollow cavity of the carrier layer is 50-500nm, and the cavity has good mass transfer capacity and electron conduction capacity under this size. If the inner diameter of the carrier layer is too small, it is not conducive to proton conduction, and if the inner diameter is too large, it is not conducive to electron conduction.

[0053] In some embodiments, the specific surface area of ​​the carrier layer is 600 to 1200 m 2 / g, specifically, for example, 600m 2 / g,800m 2 / g,1000m 2 / g,1200m 2 / g; and / or, the mesopore volume of the carrier layer is 1.0 to 2.0 m 3 / g, specifically, for example, 1.0m 3 / g, 1.5m 3 / g, 2.0m 3 / g; Optionally, at least part of the mesopores of the carrier layer are through holes. In the embodiment of the present invention, the carrier layer has a large specific surface area and a suitable pore structure. The large specific surface area can provide abundant attachment sites for active metals, and the suitable mesoporous structure is conducive to the intrapore loading of active metal particles such as Pt particles, which can effectively inhibit the shedding, migration and agglomeration of active metal particles, avoid being poisoned by polymers, and is conducive to the transmission of protons and oxygen.

[0054] In some embodiments, the carrier layer is obtained by calcining a first carbon precursor; optionally, the first carbon precursor includes a first component and a second component; the first component includes at least one of dopamine hydrochloride, resorcinol, m-aminophenol, and acrylonitrile; the second component includes at least one of formaldehyde and acetaldehyde; the mass ratio of the first component to the second component is 1:(1-6), specifically, for example, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6.

[0055] In some embodiments, the first active metal layer and the second active metal layer are each independently a single metal layer and / or an alloy metal layer; preferably, the first active metal layer and the second active metal layer each independently include at least one of Pt, PtCo, PtNi, and PtRu; wherein there is no special restriction on the content of each metal in the alloy metal layer, and it can be any proportion according to catalytic requirements.

[0056] In some embodiments, the total loading amount of the first active metal layer and the second active metal layer in the catalyst is 30-80wt%, specifically, for example, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt%; optionally, the loading amount of the second active metal layer in the catalyst is not less than 30% of the total loading amount of the first active metal layer and the second active metal layer in the catalyst, specifically, for example, 30wt%, 40wt%, 45wt%, 50wt%. In the embodiment of the present invention, the second active metal layer can effectively avoid being poisoned by the polymer, and is in the innermost layer, with the carbon layer and the carrier layer protecting the outer side, which can effectively slow down or reduce the shedding, migration and agglomeration of the active metal particles, and improve the activity and durability of the catalyst.

[0057] In some embodiments, the first active metal layer includes a first active metal, optionally, the first active metal is a single metal and / or an alloy, optionally, the first active metal includes at least one of Pt, PtCo, PtNi, PtRu; optionally, the grain size of the first active metal is 2.5-6.5nm, specifically, for example, 2.5nm, 3nm, 4nm, 5nm, 6nm, 6.5nm, preferably, 3-5nm. In the embodiment of the present invention, the particle size of the first active metal is 2.5-6.5nm, which can achieve high catalytic activity while having good durability. When the grain size is less than 2.5nm, the catalyst durability is relatively poor; when the grain size is greater than 6.5nm, the catalyst activity is relatively low. The grain size is further preferably 3-5nm, which can further obtain a catalyst with better catalytic activity and durability.

[0058] In some embodiments, the second active metal layer includes a second active metal, optionally, the second active metal is a single metal and / or an alloy, optionally, the second active metal includes at least one of Pt, PtCo, PtNi, PtRu; optionally, the grain size of the second active metal is 2.5-6.5nm, specifically, for example, 2.5nm, 3nm, 4nm, 5nm, 6nm, 6.5nm, preferably, 3-5nm. In an embodiment of the present invention, the particle size of the second active metal is 2.5-6.5nm, which can achieve high catalytic activity while having good durability. When the grain size is less than 2.5nm, the catalyst durability is relatively poor; when the grain size is greater than 6.5nm, the catalyst activity is relatively low. The grain size is further preferably 3-5nm, which can further obtain a catalyst with better catalytic activity and durability.

[0059] In some embodiments, the thickness of the protective layer is 1-3nm, specifically, for example, 1nm, 2nm, 3nm; the protective layer is a carbon layer with a rich pore structure, which is porous carbon. In the embodiment of the present invention, the carbon layer with a thickness of 1-3nm can protect the active metal from being covered and poisoned by the sulfonic acid group, thereby improving its catalytic activity; the protective layer has a confining effect, which can slow down or prevent the agglomeration, dissolution or shedding process of the platinum particles; the protective layer has good conductivity, which helps to improve the efficiency of electron transfer; the protective layer can also optimize the diffusion of gas on the catalyst surface, ensuring that hydrogen and oxygen can reach the catalytic active sites more effectively. When the thickness of the protective layer exceeds 3nm, the active sites are not easily exposed and the catalytic activity is relatively low; when the thickness is less than 1nm, it cannot effectively prevent the agglomeration and dissolution of platinum particles.

[0060] In some embodiments, the protective layer is a carbon layer; optionally, the carbon layer includes carbon elements and other elements, for example, nitrogen elements.

[0061] In some embodiments, the protective layer is obtained by sintering a second carbon precursor; optionally, the second carbon precursor includes at least one of polyvinyl alcohol, polyethylene glycol, dopamine hydrochloride, and tannic acid.

[0062] A method for preparing a catalyst according to an embodiment of the present invention comprises the following steps:

[0063] (1) mixing a template, a first carbon precursor and a solvent, and stirring to form a precipitated product;

[0064] (2) calcining the precipitated product to obtain a calcined product; mixing the calcined product with a detergent to remove the template agent to obtain a carbon carrier;

[0065] (3) loading the carbon carrier with active metal through vacuum synthesis treatment, and then performing a two-stage heat treatment to obtain a heat-treated product; wherein the two-stage heat treatment includes a first stage heat treatment and a second stage heat treatment, and the temperature of the second stage heat treatment is higher than the temperature of the first stage heat treatment;

[0066] (4) Immersing the heat-treated product in a second carbon precursor solution, followed by drying and sintering to obtain a catalyst.

[0067] In the embodiment of the present invention, the template and the first carbon precursor form a precipitation product, and a carbon carrier having both a graphitized structure and a porous structure, i.e., a carrier layer, can be obtained by calcination. Compared with the method of first removing the template and then high-temperature graphitization treatment, the method of first calcining and then removing the template in the present invention can ensure the morphology of the material during high-temperature activation, so that it is not easy to collapse. Compared with the traditional method of synthesizing active metal layers, the present invention adopts a vacuum synthesis method to load active metals to obtain an active metal layer loaded on both sides of the carrier layer. The vacuum synthesis method can load active metal particles to the inner side of the carrier layer, and can also increase the inner active metal loading to form a second active metal layer. The second active metal layer is located on the inner side of the carrier layer, and is not easy to agglomerate, migrate, and fall off; compared with a single active metal layer, the combination of the inner and outer two layers of active metal layers is more conducive to improving the activity and durability of the catalyst. After the vacuum synthesis treatment loads the active metal, a two-stage heat treatment process is performed to obtain a catalyst with suitable and uniform particle sizes of the first active metal and the second active metal, and better performance. Finally, the protective layer is formed by immersing in a second carbon precursor solution, followed by drying and sintering, which not only improves mass transfer, but also plays a protective and confining role. The preparation method of the present invention is simple and efficient, and the template cost is low, which is conducive to large-scale production and application.

[0068] In some embodiments, in step (1), the template includes at least one of mesoporous silica and tetraethyl orthosilicate; the particle size of the template or the product after the reaction of the template and the solvent is the same as the inner diameter of the carrier layer, which can be 50-500nm.

[0069] In some embodiments, in step (1), the stirring temperature is 25°C (room temperature)-80°C, and the stirring time is 6-12h.

[0070] In some embodiments, in step (1), the template and the solvent are first mixed to react, and then mixed with the first carbon precursor and stirred to form a precipitated product; optionally, the reaction temperature is 25° C. (room temperature)-80° C., the reaction time is 0.5-3 h, and the stirring time is 6-12 h;

[0071] In a specific embodiment, when the template includes tetraethyl orthosilicate, the tetraethyl orthosilicate is first dissolved in a solvent for reaction, and then the first carbon precursor is added and stirred to form a precipitated product; optionally, the solvent includes water, alcohol and ammonia water; optionally, the volume ratio of water, alcohol and ammonia water is (2-5): (5-15): 1; the alcohol includes at least one of methanol and ethanol; the concentration of ammonia water is 25% to 28%, specifically, for example, 25%, 26%, 27%, 28%;.

[0072] In some embodiments, in the step (1), the first carbon precursor includes a first component and a second component; the first component includes at least one of dopamine hydrochloride, resorcinol, m-aminophenol, and acrylonitrile; the second component includes at least one of formaldehyde and acetaldehyde; the mass ratio of the first component to the second component is 1:(1-6), specifically, for example, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6.

[0073] In some embodiments, in step (1), the mass ratio of the template to the first carbon precursor is (2-8):1, specifically, for example, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1.

[0074] In some embodiments, in step (1), the solvent includes water; optionally, the solvent also includes alcohol and aqueous ammonia; the alcohol includes at least one of methanol and ethanol; the concentration of aqueous ammonia is 25% to 28%, specifically, for example, 25%, 26%, 27%, 28%; the volume ratio of water, alcohol and aqueous ammonia is (2 to 5): (5 to 15): 1.

[0075] In some embodiments, in step (1), the mass ratio of the first carbon precursor to the solvent is 0.1-5:100.

[0076] In some embodiments, in step (1), stirring is performed to form a precipitate, and then the precipitate is filtered, washed and dried to obtain a precipitated product.

[0077] In some embodiments, in step (2), the precipitated product is calcined to obtain a calcined product; the calcined product is mixed with a detergent to remove the template agent to obtain a carbon carrier, that is, to form a carrier layer.

[0078] In some embodiments, in step (2), the calcination treatment atmosphere includes a first gas, the first gas is an oxidizing atmosphere, and the first gas includes at least one of water vapor, carbon dioxide, and air; in the calcination treatment atmosphere, the volume percentage of the first gas is 10%-50%, specifically, for example, 10%, 20%, 30%, 40%, 50%; the calcination treatment atmosphere also includes a second gas, optionally, the second gas includes argon; in the calcination treatment atmosphere, the volume percentage of the second gas is 50%-90%, specifically, for example, 50%, 60%, 70%, 80%, 90%. In the embodiment of the present invention, the calcination treatment is an activation pore-forming step, which can make the surface of the carbon carrier layer have a rich mesoporous structure, which is more conducive to the loading of active metals inside and outside the carrier layer. If the proportion of the first gas is too low, the pore-forming effect is not obvious, and if the proportion of the first gas is too high, the carbon loss is serious, and the carbon structure is prone to collapse and deformation.

[0079] In some embodiments, in step (2), the calcination temperature is 1000-2500°C, specifically, for example, 1000°C, 1200°C, 1300°C, 1500°C, 1800°C, 2000°C, 2500°C, preferably, 1300-2000°C; the calcination time is 1-6h, specifically, for example, 1h, 2h, 3h, 4h, 5h, 6h. In the embodiment of the present invention, the calcination temperature is 1000-2500°C, and a carbon carrier layer with a high degree of graphitization and a suitable specific surface area can be obtained at the same time. When the calcination temperature is lower than 1000°C, the degree of graphitization of the carrier layer material is relatively low, and the conductivity and corrosion resistance are poor; when the calcination temperature is higher than 2500°C, the degree of graphitization is too high, which is not conducive to loading; and the carbon structure of the carrier layer material will collapse, which is not conducive to mass transfer.

[0080] In some embodiments, in step (2), the calcined product and a detergent are mixed to remove the template to obtain a carbon support;

[0081] Optionally, stirring is performed during the mixing process; Optionally, the mixing process may be heated or performed at room temperature; The time for removing the template by mixing is 12-48 hours;

[0082] Optionally, the detergent comprises a sodium hydroxide aqueous solution or a hydrofluoric acid aqueous solution; the mass fraction of the detergent is 2%-15%, optionally, the mass fraction of the sodium hydroxide aqueous solution is 2%-15%, and the mass fraction of the hydrofluoric acid is 2%-15%.

[0083] In some embodiments, in step (3), the carbon carrier is loaded with active metals through vacuum synthesis treatment, and then subjected to a two-stage heat treatment to obtain a heat-treated product to form a first active metal layer and a second active metal layer.

[0084] In some embodiments, in step (3), the vacuum degree of the vacuum synthesis treatment for loading active metals is 50-200 mbar.

[0085] In some embodiments, in step (3), there is no particular limitation on the method for synthesizing the loaded active metal, and the conventional method for synthesizing the loaded active metal in the art can be used to synthesize the loaded active metal under vacuum conditions;

[0086] In a specific embodiment, in the vacuum synthesis process:

[0087] 1) dispersing the carbon carrier in water; optionally, the dispersion time is 1-4 hours;

[0088] 2) then adding a platinum-containing precursor and dispersing it in a vacuum environment;

[0089] Optionally, the vacuum degree is 50-200 mbar, the dispersion time is 2-6 h, and the dispersion temperature is 30-60 ° C; Optionally, the platinum-containing precursor includes at least one of chloroplatinic acid, platinum acetylacetonate, platinum nitrate, potassium chloroplatinate or sodium chloroplatinate; the mass ratio of the carbon carrier to the platinum element in the platinum-containing precursor is 1-10:1-10;

[0090] 3) Then, a reducing agent is added to continue dispersing; optionally, the dispersion time is 2-6 hours and the dispersion temperature is 50-90° C.; optionally, the reducing agent includes at least one of methanol, ethylene glycol, ascorbic acid, hydrazine hydrate, ethanol, formaldehyde or formic acid; and the mass ratio of the platinum element in the platinum-containing precursor to the reducing agent is 1:5-30.

[0091] In some embodiments, in the step (3), the two-stage heat treatment is a constant temperature heat treatment; the temperature of the first stage heat treatment is 80-200°C, specifically, for example, 80°C, 100°C, 150°C, 200°C; the time of the first stage heat treatment is 1-12h, specifically, for example, 1h, 2h, 4h, 6h, 8h, 10h, 12h; the temperature of the second stage heat treatment is 800-950°C, specifically, for example, 800°C, 850°C, 900°C, 950°C; the time of the second stage heat treatment is 0.5-3h, specifically, for example, 0.5h, 1h, 2h, 3h; and / or, the two-stage heat treatment is carried out under an inert atmosphere, optionally, the inert atmosphere includes at least one of nitrogen and argon. In the embodiment of the present invention, after vacuum synthesis treatment to load active metals, a two-stage heat treatment process is carried out to obtain a catalyst with suitable and uniform particle sizes of the first active metal and the second active metal and better performance. If only the first heat treatment is performed, the crystallinity of the catalyst is poor, the size of the platinum crystallites is small, the active metal is prone to agglomeration and shedding, and the durability of the catalyst is poor. If only the second heat treatment is performed, the size of the platinum crystallites in the catalyst is large and the particle uniformity is poor, which leads to poor catalytic activity of the catalyst.

[0092] In some embodiments, in step (4), the heat-treated product is immersed in a second carbon precursor solution, and then dried and sintered to form a protective layer to obtain a catalyst; optionally, filtering is performed before drying; and the drying is performed by vacuum drying.

[0093] In some embodiments, in step (4), the second carbon precursor includes at least one of polyvinyl alcohol, polyethylene glycol, dopamine hydrochloride, and tannic acid; and / or the concentration of the second carbon precursor solution is 0.1-10wt%, specifically, for example, 0.1wt%, 1wt%, 2wt%, 4wt%, 5wt%, 6wt%, 8wt%, 10wt%; optionally, the temperature of immersing the heat-treated product in the second carbon precursor solution is 25-80°C, and the time is 2-12h;

[0094] Optionally, the solvent of the second carbon precursor solution includes water;

[0095] Optionally, immersing the heat-treated product in a second carbon precursor solution and stirring;

[0096] Optionally, when the second carbon precursor solution includes dopamine hydrochloride or tannic acid, the second carbon precursor solution also includes tris(hydroxymethylaminomethane)-hydrochloric acid; optionally, the pH of the second carbon precursor solution is 7.5 to 9.5; optionally, it also includes sodium hydroxide, and the pH value is adjusted by sodium hydroxide.

[0097] In some embodiments, in the step (4), the sintering temperature is 300-900°C, specifically, for example, 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, preferably, 500-700°C; the sintering time is 0.5-5h, specifically, for example, 0.5h, 1h, 2h, 3h, 4h, 5h, preferably, 1-3h; the sintering atmosphere is an inert atmosphere, optionally, the inert atmosphere includes nitrogen.

[0098] In some embodiments, in step (4), the sintering is followed by washing and drying to obtain a catalyst.

[0099] An application of a catalyst according to an embodiment of the present invention, the catalyst includes the catalyst according to the embodiment of the present invention or the catalyst prepared by the preparation method according to the embodiment of the present invention, and the catalyst is used in a fuel cell. In the embodiment of the present invention, the catalyst has excellent activity and durability.

[0100] A fuel cell according to an embodiment of the present invention comprises the catalyst provided in the embodiment of the present invention or the catalyst prepared by the preparation method provided in the embodiment of the present invention. In the embodiment of the present invention, the catalyst has excellent activity and durability.

[0101] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0102] Example 1

[0103] A method for preparing a catalyst comprises the following steps:

[0104] (1) Dissolve 5 g of tetraethyl orthosilicate in a mixed solution consisting of 90 mL of ethanol, 10 mL of ammonia water and 30 mL of water and stir for 2 h. Then add 0.6 g of resorcinol and 0.8 g of formaldehyde and continue stirring evenly for 8 h. Collect the precipitate and wash it with ethanol and water until it is neutral.

[0105] (2) The washed product is dried to obtain a precipitated product, which is then calcined in a mixed atmosphere of carbon dioxide and argon, with a volume ratio of carbon dioxide to argon of 1:9, a constant temperature of 1300°C, and a treatment time of 1 hour. The calcined product is washed with a 12% by mass hydrofluoric acid aqueous solution for 24 hours, filtered and dried to obtain a carbon carrier, i.e., a carrier layer.

[0106] (3) 0.4 g of carbon carrier was dispersed in 100 mL of water for 2 h; then, 0.6 g of chloroplatinic acid solution containing platinum was added and dispersed at 50 ° C for 3 h under vacuum environment, and the vacuum degree was 100 mbar; then, 10 g of ethylene glycol was added and dispersed at 80 ° C for 3 h, and 1 g of catalyst intermediate with a platinum content of 60% was obtained after washing and drying. The catalyst intermediate was subjected to two-stage constant temperature heat treatment to obtain a heat-treated product; wherein, the first stage heat treatment temperature was 200 ° C, and the treatment time was 5 h; the second stage heat treatment temperature was 850 ° C, and the treatment time was 1 h, and the heat treatment atmosphere was argon.

[0107] (4) Take 0.1 g of the heat-treated product and immerse it in a 4.8 wt% polyvinyl alcohol aqueous solution, stir it at 50°C for 5 h, filter the product after it is fully soaked, and then vacuum dry it. Then, treat it at 600°C for 0.5 h in a nitrogen atmosphere. After taking it out, wash and dry it to obtain a catalyst.

[0108] The physical and chemical properties of the carbon carrier prepared in step (2) are shown in Table 1, and the physical and chemical properties of the catalyst prepared in step (4) are shown in Table 2.

[0109] Example 2

[0110] A method for preparing a catalyst comprises the following steps:

[0111] (1) Dissolve 5 g of tetraethyl orthosilicate in a mixed solution consisting of 90 mL of ethanol, 10 mL of ammonia water and 30 mL of water and stir for 2 h. Then add 0.6 g of m-aminophenol and 0.8 g of formaldehyde and continue stirring evenly for 10 h. Collect the precipitate and wash it with ethanol and water until it is neutral.

[0112] (2) The washed product is dried to obtain a precipitated product, which is then calcined in a mixed atmosphere of carbon dioxide and argon, with a volume ratio of carbon dioxide to argon of 1:9, a constant temperature of 1500°C, and a treatment time of 1 hour. The calcined product is washed with a 12% by mass hydrofluoric acid aqueous solution for 24 hours, filtered and dried to obtain a carbon carrier, i.e., a carrier layer.

[0113] (3) 0.4 g of carbon carrier was dispersed in 100 mL of water for 2 h; then, 0.6 g of chloroplatinic acid solution containing platinum was added and dispersed at 50 ° C for 3 h under vacuum environment, and the vacuum degree was 80 mbar; then 10 g of ethylene glycol was added and dispersed at 80 ° C for 3 h, and 1 g of catalyst intermediate with a platinum content of 60% was obtained after washing and drying. The catalyst intermediate was subjected to two-stage constant temperature heat treatment to obtain a heat-treated product; wherein, the first stage heat treatment temperature was 100 ° C, and the treatment time was 10 h; the second stage heat treatment temperature was 850 ° C, and the treatment time was 1.5 h, and the heat treatment atmosphere was argon.

[0114] (4) Take 0.1 g of the heat-treated product and immerse it in a 4.8 wt% polyvinyl alcohol aqueous solution, stir it at 50°C for 6 h, filter the product after it is fully soaked, and vacuum dry it. Then, treat it at 600°C for 0.5 h in a nitrogen atmosphere, take it out, wash it, and dry it to obtain a catalyst.

[0115] Example 3

[0116] A method for preparing a catalyst comprises the following steps:

[0117] (1) Dissolve 5 g of tetraethyl orthosilicate in a mixed solution consisting of 90 mL of ethanol, 10 mL of ammonia water and 30 mL of water and stir for 2 h. Then add 0.6 g of resorcinol and 0.8 g of formaldehyde and continue stirring evenly for 12 h. Collect the precipitate and wash it with ethanol and water until it is neutral.

[0118] (2) The washed product is dried to obtain a precipitated product, which is then calcined in a mixed atmosphere of carbon dioxide and argon, with a volume ratio of carbon dioxide to argon of 1:9, a constant temperature of 1800°C, and a treatment time of 1 hour. The calcined product is washed with a 12% by mass hydrofluoric acid aqueous solution for 24 hours, filtered and dried to obtain a carbon carrier, i.e., a carrier layer.

[0119] (3) 0.4 g of carbon carrier was dispersed in 100 mL of water for 2 h; then, 0.6 g of chloroplatinic acid solution containing platinum was added and dispersed at 50 ° C for 3 h under vacuum environment, and the vacuum degree was 100 mbar; then, 10 g of ethylene glycol was added and dispersed at 80 ° C for 3 h, and 1 g of catalyst intermediate with a platinum content of 60% was obtained after washing and drying. The catalyst intermediate was subjected to two-stage constant temperature sintering heat treatment to obtain a heat-treated product; wherein, the first stage heat treatment temperature was 180 ° C, and the treatment time was 6 h; the second stage heat treatment temperature was 850 ° C, and the treatment time was 1 h, and the heat treatment atmosphere was nitrogen.

[0120] (4) Take 0.1 g of the heat-treated product and immerse it in a 4.8 wt% polyvinyl alcohol aqueous solution, stir it at 50°C for 6 h, filter the product after it is fully soaked, and vacuum dry it. Then, treat it at 600°C for 0.5 h in a nitrogen atmosphere, take it out, wash it, and dry it to obtain a catalyst.

[0121] Example 4

[0122] The preparation method is the same as that of Example 3, except that in step (4), the heat-treated product is immersed in a weak alkaline solution containing dopamine hydrochloride; wherein the preparation method of the weak alkaline solution containing dopamine hydrochloride comprises: dissolving 0.1 g of dopamine hydrochloride in 20 mL of tris(hydroxymethylaminomethane)-hydrochloric acid solution, adjusting the pH to 8.5 with sodium hydroxide solution, and stirring at room temperature for 8 hours.

[0123] Example 5

[0124] The preparation method is the same as that of Example 3, except that in step (4), the heat-treated product is immersed in a weak alkaline solution containing tannic acid; wherein the preparation method of the weak alkaline solution containing tannic acid comprises: dissolving 0.1 g of tannic acid in 30 mL of tris(hydroxymethyl)aminomethane-hydrochloric acid solution, adjusting the pH to 8.5 with sodium hydroxide solution, and stirring at room temperature for 8 hours.

[0125] Comparative Example 1

[0126] The preparation method is the same as that of Example 1, except that in step (2), the calcination atmosphere uses argon instead of the mixed atmosphere of carbon dioxide and argon in Example 1.

[0127] Comparative Example 2

[0128] The preparation method is the same as that of Example 1, except that in step (2), the constant temperature of the calcination treatment is 850°C instead of 1300°C in Example 1.

[0129] Comparative Example 3

[0130] The preparation method is the same as that of Example 1, except that in step (2), the constant temperature of the calcination treatment is 2700° C. instead of 1300° C. in Example 1.

[0131] Comparative Example 4

[0132] The preparation method is the same as that of Example 1, except that the preparation of the catalyst intermediate in step (3) is carried out under normal pressure.

[0133] Comparative Example 5

[0134] The preparation method is the same as that of Example 1, except that step (4) is omitted, that is, the heat-treated product prepared in step (3) is used as the catalyst, and the catalyst is not immersed in a polyvinyl alcohol solution, sintered, or subjected to subsequent processes.

[0135] Comparative Example 6

[0136] The preparation method is the same as that of Example 1, except that in step (3), the catalyst intermediate is only subjected to the first stage heat treatment and not the second stage heat treatment.

[0137] Comparative Example 7

[0138] The preparation method is the same as that of Example 1, except that in step (3), the catalyst intermediate is not subjected to the first stage heat treatment but only to the second stage heat treatment.

[0139] Table 1 Physicochemical parameters of carbon carriers obtained in Examples and Comparative Examples

[0140]

[0141]

[0142] Table 2 Physicochemical parameters of the catalysts obtained in the examples and comparative examples

[0143]

[0144] As can be seen from Table 1 and Table 2, the catalysts prepared in Examples 1-5 of the present invention have excellent activity and durability that are synergistically improved. This is because the catalyst of the present invention is a sandwich-type multifunctional catalyst, presenting a four-layer hollow spherical shell structure, having a hollow porous spherical shell structure carbon carrier that has been graphitized, which can improve the activity of the catalyst and the corrosion resistance of the carrier; the two layers of active metal layers are respectively arranged on both sides of the carrier layer, which can balance the activity and durability, and slow down the agglomeration and shedding of the catalyst; the active metal layer is provided with a carbon layer protective layer, which plays a protective and confining role while improving mass transfer, and reduces the agglomeration and shedding of active metal particles; the four-layer structure synergistically improves the activity and durability of the catalyst.

[0145] By comparing Example 1 and Comparative Example 1, it can be seen that in Comparative Example 1, no activating pore-forming atmosphere carbon dioxide is introduced, and the carbon carrier of Comparative Example 1 has a lower specific surface area and less pore structure, resulting in relatively low loading capacity and mass transfer capacity of the carbon carrier, which in turn leads to poor performance of the catalyst.

[0146] By comparing Example 1 and Comparative Example 2, it can be seen that the calcination temperature in Comparative Example 2 is lower, the degree of graphitization of the carbon carrier in Comparative Example 2 is lower, and the size of the graphite crystallites is smaller, resulting in poor corrosion resistance of the carbon carrier, and thus poor performance of the catalyst.

[0147] By comparing Example 1 and Comparative Example 3, it can be seen that the calcination temperature in Comparative Example 3 is relatively high, the carbon carrier structure collapses, and the pore structure is destroyed, resulting in the inability to load the inner layer of the carbon carrier with platinum, and the catalyst performance is poor.

[0148] By comparing Example 1 and Comparative Example 4, it can be seen that the active metal preparation process of the catalyst in Comparative Example 4 is a normal pressure synthesis process, the active metal loading of the second layer of the catalyst finally prepared is low, and the catalyst performance is poor.

[0149] By comparing Example 1 and Comparative Example 5, it can be seen that the protective layer preparation step is not performed in Comparative Example 5, and the active metal in the finally prepared catalyst is prone to agglomeration and shedding due to lack of protection of the carbon layer, and the performance of the catalyst is poor.

[0150] By comparing Example 1 and Comparative Example 6, it can be seen that in Comparative Example 6, only the first stage of heat treatment is performed, the crystallinity of the catalyst is poor, the particle size of the platinum crystallites is small, the active metal is prone to agglomeration and shedding, and the durability of the catalyst is poor.

[0151] By comparing Example 1 and Comparative Example 7, it can be seen that in Comparative Example 7, only the second stage heat treatment is performed, the particle size of the platinum crystallites in the catalyst is larger and the particle uniformity is poor, which leads to poor catalytic activity of the catalyst.

[0152] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0153] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.

Claims

1. A catalyst, characterized in that The catalyst is in a hollow spherical shell structure, and the hollow spherical shell structure is provided with a protective layer, a first active metal layer, a carrier layer, and a second active metal layer in sequence from the outside to the inside along the spherical diameter direction; wherein the protective layer is a carbon layer, and the carrier layer is a porous carbon layer.

2. The catalyst according to claim 1, characterized in that The carrier layer has a graphitized structure; the carrier layer includes graphite crystallites, and the size of the graphite crystallites is 1.5-3.5 nm; And / or, the thickness of the carrier layer is 10-20 nm; And / or, the inner diameter of the carrier layer is 50-500 nm; And / or, the specific surface area of ​​the carrier layer is 600 to 1200 m 2 / g; And / or, the mesopore volume of the carrier layer is 1.0 to 2.0 m 3 / g.

3. The catalyst according to claim 1, characterized in that The first active metal layer and the second active metal layer are each independently a single metal layer and / or an alloy metal layer; preferably, the first active metal layer and the second active metal layer are each independently at least one of Pt, PtCo, PtNi, and PtRu; and / or, the total loading amount of the first active metal layer and the second active metal layer in the catalyst is 30-80wt%; and / or, the loading amount of the second active metal layer in the catalyst is not less than 30% of the total loading amount of the first active metal layer and the second active metal layer in the catalyst; And / or, the first active metal layer includes a first active metal, and the grain size of the first active metal is 2.5-6.5 nm; And / or, the second active metal layer includes a second active metal, and the grain size of the second active metal is 2.5-6.5 nm.

4. The catalyst according to claim 1, characterized in that The thickness of the protective layer is 1-3 nm.

5. A method for preparing the catalyst according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) mixing a template, a first carbon precursor and a solvent, and stirring to form a precipitated product; (2) calcining the precipitated product to obtain a calcined product; The calcined product is mixed with a detergent to remove the template agent to obtain a carbon support; (3) loading the carbon carrier with active metal through vacuum synthesis treatment, and then performing a two-stage heat treatment to obtain a heat-treated product; wherein the two-stage heat treatment includes a first stage heat treatment and a second stage heat treatment, and the temperature of the second stage heat treatment is higher than the temperature of the first stage heat treatment; (4) Immersing the heat-treated product in a second carbon precursor solution, followed by drying and sintering to obtain a catalyst.

6. The method for preparing the catalyst according to claim 5, characterized in that: In the step (1), the template comprises at least one of mesoporous silica and tetraethyl orthosilicate; And / or, in the step (1), the first carbon precursor comprises a first component and a second component; the first component comprises at least one of dopamine hydrochloride, resorcinol, m-aminophenol, and acrylonitrile; the second component comprises at least one of formaldehyde and acetaldehyde; the mass ratio of the first component to the second component is 1:(1-6); And / or, in the step (1), the mass ratio of the template to the first carbon precursor is (2-8):1; And / or, in the step (2), the calcination atmosphere includes a first gas, and the first gas includes at least one of water vapor, carbon dioxide, and air; in the calcination atmosphere, the volume percentage of the first gas is 10%-50%; And / or, in the step (2), the calcination temperature is 1000-2500°C; And / or, in step (2), the calcination treatment time is 1 to 6 hours; And / or, in step (2), the detergent comprises an aqueous sodium hydroxide solution or an aqueous hydrofluoric acid solution.

7. The method for preparing a catalyst according to claim 5, characterized in that: In the step (3), the temperature of the first heat treatment is 80 to 200° C., and the time of the first heat treatment is 1 to 12 hours; And / or, the temperature of the second heat treatment is 800-950°C, and the time of the second heat treatment is 0.5-3h; And / or, the two-stage heat treatment is performed under an inert atmosphere.

8. The method for preparing the catalyst according to claim 5, characterized in that: In the step (4), the second carbon precursor includes at least one of polyvinyl alcohol, polyethylene glycol, dopamine hydrochloride, and tannic acid; and / or, the concentration of the second carbon precursor solution is 0.1-10wt%; And / or, the sintering temperature is 300-900°C, and the sintering time is 0.5-5h; And / or, the sintering atmosphere is an inert atmosphere.

9. An application of a catalyst, characterized in that: The catalyst comprises the catalyst according to any one of claims 1 to 4 or the catalyst prepared by the preparation method according to any one of claims 5 to 8, and the catalyst is used in a fuel cell.

10. A fuel cell, characterized in that: The invention comprises the catalyst described in any one of claims 1 to 4 or the catalyst prepared by the preparation method described in any one of claims 5 to 8.